VD_FINDINFO HC / 2019 / 456 vom 16. Mai 2019 - VD Tribunal cantonal (2019)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, ENFANT, REVENU DÉTERMINANT | 176 al. 1 ch. 1 CC, 276 al. 1 CC, 276 al. 2 CC, 286 al. 1 CC, 286 al. 2 CC